2007
DOI: 10.1093/rheumatology/kem260
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis, cardiovascular disease and physical exercise: a systematic review

Abstract: This systematic review investigates the effectiveness of exercise interventions in improving disease-related characteristics in patients with rheumatoid arthritis (RA). It also provides suggestions for exercise programmes suitable for improving the cardiovascular profile of RA patients and proposes areas for future research in the field. Six databases (Medline, Cochrane Library, CINAHL, Google Scholar, EMBASE and PEDro) were searched to identify publications from 1974 to December 2006 regarding RA and exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(155 citation statements)
references
References 128 publications
6
138
0
11
Order By: Relevance
“…Fatigability with exertion and cardiovascular adverse events are important proxies for exercise tolerance, which have not yet been accurately evaluated. According to Metsios et al, these two outcome measures deserve more attention in future trials (34).…”
Section: Discussionmentioning
confidence: 99%
“…Fatigability with exertion and cardiovascular adverse events are important proxies for exercise tolerance, which have not yet been accurately evaluated. According to Metsios et al, these two outcome measures deserve more attention in future trials (34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effect of aerobic exercise on patients with RA made use of cycling, aquatics, aerobic dance or walking. [36][37][38][39] Janse van Rensburg et al found that patients with RA improved significantly in terms of flexibility, strength and aerobic capacity measured after a 12-week aerobic exercise intervention (walking or aquatics), combined with strengthening and stretching exercises. 39 Furthermore, the exercise group improved significantly more than the control group with respect to disease activity scores (DAS28).…”
Section: Physical Activity Levels Of Patients With Rheumatoid Arthritismentioning
confidence: 99%
“…There is compelling evidence that exercise can play a significant role in the physical and psychosocial health of RA patients [2,3]. However, only a limited number of studies exist on the relation of exercise interventions to cardiovascular disease in these patients [4].…”
Section: Introductionmentioning
confidence: 99%